"М'яка сила" як політичний інструмент Європейського Союзу (1990-ті – 2020-ті рр.) - Мартинов, А. (Міжнародні зв’язки України: наукові пошуки і знахідки, 2020)
Поняття «м’яка сила» має глибоке історичне коріння. В європейській
традиції можна говорити про діалектику взаємовпливу «м’якої сили» і
жорсткої сили на прикладі праць Н. Макіавеллі. У 1990 р. у сучасному
сенсі це поняття використав американський політолог Дж. Най. ЄС, на
відміну від США і Китаю, має менше можливостей для послідовного
застосування інструментів «м’якої сили». Власне її використання в
процесі реалізації спільної зовнішньої політики ЄС передбачено Маастрихтським і Амстердамським договорами. Перешкоди в застосуванні
політики «м’якої сили» ЄС пов’язані з проблемами формування та послідовної реалізації спільної зовнішньої політики ЄС, зокрема, у процесі проведення гуманітарних операцій по всьому світу. Актуальним питанням є поліпшення іміджу ЄС на тлі процедури Брексіту та удосконалення взаємодії національних дипломатичних шкіл країн-членів ЄС у
процесі застосування інструментарію «м’якої сили». “Soft power” is the ability to change someone else’s values, ideas, interests.
Successful use of “soft power” leads to a change in attitudes and behavior.
“Soft power” can be seen as managing the mass consciousness by indirect
means that do not encounter conscious resistance. “Soft power” resources
belong to civil society networks. Following the British referendum on June 23,
2016, the EU’s global power of influence diminished. Traditionally, the European
Union is seen as a stable center of material wealth, high social status,
social optimism and justice, spiritual and physical comfort. However, as a rule,
they forget about the fact that there is no permanent dependence between
subjective well-being and changes in economic conditions of life. Until now,
European optimists are pushing European integration as the only effective
answer to the challenges of globalization, while European pessimists have said
that federal Europe would be too centralized, inflexible and wasteful. The
European Union is not so much a generator of European peace, as its result.
The EU has emerged as a unique conglomerate of democratic states. This is
not a federation or collective bargaining agreement, and it is not a classic
nation-state, and most importantly not an empire with a metropolis at its
center. It is an experimental form of peace-based integration as a norm.
Instead, the empire is usually a centralized militarized state, the possession of
which is a conglomerate of national territories of subjugated peoples. The EU
is a social institution that implements collective action based on democratic
approval and consent to their adoption. Despite governance weaknesses, the
EU remains an important layer of capital regulation in the face of three global
crises: the financial, environmental and security crises.